Lebanon : Policy Note on Irrigation Sector Sustainability - World Bank (Washington, DC, 2013)
This Policy Note has three main objectives : a) formulate strategic choices related to the sustainability of irrigated agriculture in Lebanon. b) recommend institutional strengthening of water resource management in the irrigation sector in general, especially for operations and maintenance (O&M). c) define the Bank's future involvement in the irrigated agriculture sector. As demand for domestic, industrial, and agriculture water increases, Lebanon could face chronic water shortages in the next two decades, particularly in the summer months. In fact, signs of such shortages are already apparent, data on water demand and water balance are conflicting, but they generally indicate that the overall annual water balance will practically go into deficit just after 2020, while the dry season balance will be in deficit in 2004. In addition to existing structural problems, the quality of existing water resources is being undercut by pollution, such as, direct discharges of municipal and industrial wastewater, uncontrolled solid waste disposal, leaching of pesticides and fertilizers from agricultural lands, and seawater intrusion along the coast as a result of over exploiting groundwater. Faced with this challenge, the Government of Lebanon (GOL) has taken measures to enhance the sustainability of water resources in the country, including irrigation, which accounts for about two thirds of the annual water use.